(untitled) (Лучшие интеллектуальные исследования, 2024)
Abstract. Task-Based Teaching (TBT) has emerged as an innovative approach to language learning, focusing on engaging students in meaningful, real-life tasks to enhance their communication skills. This article explores the application of TBT in developing the English speaking skills of ninth-grade students, addressing its impact, implementation strategies, challenges, and benefits. The findings suggest that TBT significantly improves students’ fluency, accuracy, and confidence, offering an effective alternative to traditional methods.